Experimental characterization and hyperelastic constitutive modeling of open-cell elastomeric foams. (December 2019) - Landauer, Alexander K.; Li, Xiuqi; Franck, Christian; Henann, David L.
Highlights: An extensive new experimental dataset for an open-cell elastomeric foam. A new phenomenological hyperelastic model for open-cell elastomeric foams. Validation of the constitutive model under varied loading conditions. Experimental data and computational procedures freely available. Abstract: Open-cell elastomeric foams – materials consisting of an elastomeric matrix and a connected pore space – exhibit mechanical behavior marked by high compressibility and strong coupling between the volumetric and distortional responses. In this paper, we present a methodology for the experimental characterization and constitutive modeling of non-localizing, isotropic, open-cell elastomeric foam materials under quasi-static, equilibrium loading. We conduct large-deformation, homogeneous simple compression/tension experiments on three relative densities of a polyurethane-based elastomeric foam to inform a phenomenological, isotropic, hyperelastic constitutive model. The model is based on the invariants of the logarithmic strain and accounts for high compressibility and strong volumetric-distortional coupling. To validate the predictive capability of the model, we consider three types of validation experiments that involve inhomogeneous deformation: spherical and conical indentation, simple-shear-like deformation both without and with a fixed amount of pre-compression, and tension of a specimen with circular holes. We compare load-displacement responses as well as full displacement fields from the validation experiments against corresponding model predictions obtained using finite-element-based numerical simulations and demonstrate that the model is capable of accurately capturing the experimental response.